2002
DOI: 10.1345/aph.1a402
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic, Psychological, and Aggressive Disturbances with Sildenafil

Abstract: It is recommended that, before prescribing sildenafil for erectile dysfunction, clinicians should caution their patients and their partners on the possibility of neurologic, emotional, or psychological disturbances; amnesia or loss of consciousness; or aggressive behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 37 publications
0
45
0
1
Order By: Relevance
“…Some authors have established combinations as sildenafil-inhaled NO (38), sildenafil surfactant (35), or sildenafil bosentan (30), with effective pulmonary results. Although sildenafil is a very good drug for pulmonary hypertension treatment, it is necessary to evaluate the side effects such as systemic hypotension, gastric alterations (39), retinal vascular damage (40,41), neurologic, and psychological disturbances (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have established combinations as sildenafil-inhaled NO (38), sildenafil surfactant (35), or sildenafil bosentan (30), with effective pulmonary results. Although sildenafil is a very good drug for pulmonary hypertension treatment, it is necessary to evaluate the side effects such as systemic hypotension, gastric alterations (39), retinal vascular damage (40,41), neurologic, and psychological disturbances (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…It is the citrate salt of sildenafil, which is a selective inhibitor of phosphodiesterase type 5 (PDE-5), an enzyme found in the corpus cavernosum (1,2). Its pharmacologic mechanism of action is associated with nitric oxide (NO).…”
Section: Discussionmentioning
confidence: 99%
“…Some published studies identified that Viagra® can cross blood-brain barrier (BBB). In 1989, studies proved that NO is also formed in the CNS by NO synthase (NOS), and possibly has a role in CNS transduction and function (2,8). It is likely that Viagra® modulates the brain function by increasing the NO-cGMP cascade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations